Carbon molecular sieves from carbon cloth: Influence of the chemical impregnant on gas separation properties - Rodríguez-Blanco, G.; Giraldo, L.; Moreno-Piraján, J.C. (Applied surface science, 2010)
Carbon materials with molecular sieve properties (CMS) were prepared by pyrolysis of cotton fabrics by chemical activation procedures. To evaluate the changes in the chemical and textural properties, the impregnants AlCl 3, ZnCl 2 and H 3PO 4 were used at 1123 K. The materials were characterized using adsorption of nitrogen and carbon dioxide, TPD, and immersion calorimetry in C 6H 6. Adsorption kinetics of O 2, N 2, CO 2, CH 4, C 3H 8 and C 3H 6 were measured in all the prepared materials to determine their behaviour as molecular sieves. The results confirm that the chemical used as impregnant has a significant effect on the resulting CMS separation properties. All materials exhibit microporosity and low oxygen surface group contents; however, the sample impregnated with zinc chloride, with an immersion enthalpy value of 66.4 J g −1 in benzene, exhibits the best performance in the separation of CH 4–CO 2 and C 3H 8–C 3H 6 at 273 K.